2017
DOI: 10.1177/2325967117726055
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play Following Shoulder Stabilization: A Systematic Review and Meta-analysis

Abstract: Background:Anterior shoulder instability can be a disabling condition for the young athlete; however, the best surgical treatment remains controversial. Traditionally, anterior shoulder instability was treated with open stabilization. More recently, arthroscopic repair of the Bankart injury with suture anchor fixation has become an accepted technique.Hypothesis:No systematic reviews have compared the rate of return to play following arthroscopic Bankart repair with suture anchor fixation with the Bristow-Latar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 32 publications
4
76
5
1
Order By: Relevance
“…Furthermore, 1 meta-analysis reported no significant differences at the preinjury level or at any level of return to sports for patients treated with arthroscopic Bankart repair or the Latarjet procedure. 19 In the current study, most patients returned to sports activities after the arthroscopic Bankart repair (94.1%) and Latarjet procedure (96.8%). There was no significant difference in the level of return to sports between operations, thus confirming that the surgical method does not have an effect on the level of postoperative return to sports.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, 1 meta-analysis reported no significant differences at the preinjury level or at any level of return to sports for patients treated with arthroscopic Bankart repair or the Latarjet procedure. 19 In the current study, most patients returned to sports activities after the arthroscopic Bankart repair (94.1%) and Latarjet procedure (96.8%). There was no significant difference in the level of return to sports between operations, thus confirming that the surgical method does not have an effect on the level of postoperative return to sports.…”
Section: Discussionmentioning
confidence: 49%
“…Whereas some larger studies have reported losses in ER after remplissage, others have reported no statistically significant difference 20, 28, 29, 30, 31, 32, 33. Remplissage continues to have comparable return-to-sport rates to the open Latarjet procedure; however, some concern exists for throwing athletes 34, 35, 36. In their 2016 case series, Garcia et al 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 75% of studies included in a recent systematic review used time alone as their criteria for return to play, with 6 months being the most commonly recommended time-frame [49]. After primary surgical stabilization, rates of return-to-play at pre-injury level are between 65 and 75% [51]. In a recent systematic review by the senior author on revision instability surgery, these rates were Fig.…”
Section: Rehabilitation and Return To Sportmentioning
confidence: 99%